The good Earth introduction to earth science - McConnell, David 1959 February 5-; Steer, David Nathan 1960- (McGraw-Hill Education, 2021)
"For many, the wonder of Earth and its features is enough to drive learning. For these happy few, a readable book with lots of attractive photographs is almost all that is required. But for many-in fact most-learning takes more than pretty words and pictures. Providing high-quality teaching is the most cost-effective, tangible, and timely effort that geoscience instructors can make to improve student engagement, increase attendance, and add majors. But how do we do that? There is extensive literature describing what effective teaching looks like, but most science instructors have not had access to these articles and books. Further, few of us were ever explicitly taught the components of good teaching. Instead, we were left to figure it out for ourselves on the basis of our classroom experiences as students. The Good Earth was published to support both the traditional earth science class and to serve as an accessible resource for instructors seeking to apply effective teaching strategies to enhance learning"--Provided by publisher.